Safe Cholecystectomy Multi-society Practice Guideline and State of the Art Consensus Conference on Prevention of Bile Duct Injury During Cholecystectomy. Issue 1 (July 2020) - Brunt, L. Michael; Deziel, Daniel J.; Telem, Dana A.; Strasberg, Steven M.; Aggarwal, Rajesh; Asbun, Horacio; Bonjer, Jaap; McDonald, Marian; Alseidi, Adnan; Ujiki, Mike; Riall, Taylor S.; Hammill, Chet; et al.
Abstract : Background: BDI is the most common serious complication of laparoscopic cholecystectomy. To address this problem, a multi-society consensus conference was held to develop evidenced-based recommendations for safe cholecystectomy and prevention of BDI. Methods: Literature reviews were conducted for 18 key questions across 6 broad topics around cholecystectomy directed by a steering group and subject experts from 5 surgical societies (Society of Gastrointestinal and Endoscopic Surgeons, Americas Hepato-Pancreato-Biliary Association, International Hepato-Pancreato-Biliary Association, Society for Surgery of the Alimentary Tract, and European Association for Endoscopic Surgery). Evidence-based recommendations were formulated using the grading of recommendations assessment, development, and evaluation methodology. When evidence-based recommendations could not be made, expert opinion was documented. A number of recommendations for future research were also documented. Recommendations were presented at a consensus meeting in October 2018 and were voted on by an international panel of 25 experts with greater than 80% agreement considered consensus. Results: Consensus was reached on 17 of 18 questions by the guideline development group and expert panel with high concordance from audience participation. Most recommendations were conditional due to low certainty of evidence. Strong recommendations were made for (1) use of intraoperative biliary imaging for uncertainty of anatomy or suspicion of biliary injury; and (2) referral of patients with confirmed or suspected BDI to an experienced surgeon/multispecialty hepatobiliary team. Conclusions: These consensus recommendations should provide guidance to surgeons, training programs, hospitals, and professional societies for strategies that have the potential to reduce BDIs and positively impact patient outcomes. Development of clinical and educational research initiatives based on these recommendations may drive further improvement in the quality of surgical care for patients undergoing cholecystectomy. Abstract : Supplemental Digital Content is available in the text